Restitutio in Integrum in the Cancellation of Land Sale and Purchase Deeds Due to Wanprestasi (Breach of Contract): Legal Protection Analysis and Socio-Legal Implications for Third-Party Consumers - Mohammad Ahmad Eko Susilo; Helda Malta; Felicia Vanessa Japri; Windy Kosim (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Wanprestasi (breach of contract) as a cause of land transaction disputes is a persistent and recurring problem in the governance of the agrarian legal system in Indonesia. The use of irrevocable powers of attorney to facilitate one-sided title transfers is a common manifestation of this issue. Objective: The purpose of this paper is to analyze the mechanism of legal protection for the seller in the land transaction dispute involving fundamental wanprestasi and bad faith, with a case study of Supreme Court Decision No. 2134 K/Pdt/2024. Methods: This article uses a normative juridical approach with a case study, focusing on Supreme Court Decision No. 2134 K/Pdt/2024 as the primary legal material, in addition to KUHPerdata Articles 1243–1248 (on compensation), 1320 (on the requirements for the validity of a contract), 1338 (on the general principles of good faith), and 1464 (on the retention of a down payment). Results: The AJB (sale and purchase deed) and PPJB (binding sale and purchase agreement) should have been nullified (ex tunc/retroactive) since the buyer failed to pay the remaining balance of Rp2 billion—having only tendered Rp10.00 (ten rupiah)—and submitted falsified blank account documents. The court confirmed that the retention of the Rp2.32 billion seller's deposit was an essential protection measure to compensate for moral and material damages, as stipulated in Article 1464 of the Civil Code. Conclusion: This jurisprudence enhances seller protection against predatory property development practices but highlights a significant gap in consumer protection within the existing land registration system. This study recommends legislative harmonization between the restitution provisions of the Civil Code and the Consumer Protection Law (UUPK).